UJI BEBERAPA KONSENTRASI EKSTRAK TEPUNG DAUN SIRIH HUTAN (Piper aduncum L.) TERHADAP MORTALITAS WERENG COKLAT (Nilaparvata lugens Stal.) PADA TANAMAN PADI (Oryza sativa L.) - Muhammad Ismed; Rusli Rustam; Hafiz Fauzana (UIR Press, 2016)
Rice is the main agricultural products in agrarian countries, including Indonesia. Brown planthopper (Nilaparvata lugens Stal.) is one of the major pests that are harmful to the rice plant. Control measures used the farmers is still using synthetic chemical insecticides. Reducing the adverse effects caused by synthetic chemical insecticides, the need for an alternative control techniques to brown plant hopper which utilize betel leaf forest (Piper aduncum L.) as an insecticide plant. This study aims to obtain flour betel leaf forest extract concentration effective cause mortality to brown plant hopper in rice. This study was conducted experimentally using a completely randomized design (CRD) with 5 treatments and 4 replications. The treatments were a few extracts of betel leaf forest that flour : 0, 25, 50, 75 and 100 g/l of water. Betel leaf forest extract concentration flour 50 g/l of water was an effective concentration compared with other treatments, because at this concentration has been able to cause total mortality of 87.5%.